Yes, that's correct. Now just replace "a" in the formula "y = a [ x + 1 ]² [ x - 3 ]^3" with that number.

Do you see how "y = a [ x + 1 ]² [ x - 3 ]^3"and"passes through the point (4, 5)" results in "5= a[5^2][1]^3"?

Saying that x= 2/3 is a zero means that it has a factor of the form "x- 2/3". Multiply through by 3.

2. Determine an equation in factored form for the polynomial function with zeros 2 (order 2), 2/3 and 3 that passes through the point (1,6).

y = a [ x - 2 ]² [ 3x - 2 ][ x - 3 ] ...with 6 = a [ 1-2]² [ 3 - 2 ] [ 1 - 3 ]

How do we go from (the green) 2/3 to [3x-2]? And again, i'm confused with the bold part and how to put it into a?

What do you get if youdo the arithmeticindicated in "6= a[1- 2]^3 [3- 2][1- 3]"?